The influence of recreational angling on mental health among older adults: a self-determination theory perspective - Wang, Jun; Chen, Longjiang; Mei, Zhengyang; Yin, Xingxiao; Song, Lei; Zhang, XianTing (Frontiers in Psychology, 2026)
ObjectiveThis study explored how recreational fishing influences the elderly’s psychological well-being through self-determination theory (SDT) and analyzed the mediating roles of autonomy, competence, and belonging.MethodsA total of 364 elderly anglers in Yunnan Province were investigated with the Leisure Fishing Behavior Questionnaire, Basic Psychological Needs Scale, and Index of Well-Being scale. The mediating effect of self-determination theory on recreational fishing behavior and well-being was analyzed by structural equation modeling (SEM).ResultsAmong 364 older recreational anglers, structural equation modeling showed that recreational angling behavior was positively associated with subjective well-being (total standardized effect = 0.17, p < 0.001). Autonomy, competence, and belonging partially mediated this association, accounting for approximately 21%, 14%, and 12% of the total effect, respectively.